Polymers Decorated with Functional Motifs for Mitigation of Steel Corrosion: An Overview - N. A. Aljeaban; L. K. M. O. Goni; B. G. Alharbi; M. A. Jafar Mazumder; S. A. Ali; T. Chen; M. A. Quraishi; H. A. Al-Muallem (International Journal of Polymer Science)
Corrosion is a hazardous phenomenon having a devastating impact on technological and industrial applications, particularly in the oil and gas industries. Therefore, controlling the corrosion of metals is an important activity of technical, economical, environmental, and aesthetical importance in order to save huge expenses in materials, equipment, and structure. The use of corrosion inhibitors is one of the best options for controlling the metallic corrosion in various corrosive media. Numerous problems aroused with the use of inorganic and small molecule organic corrosion inhibitors, and the use of polymeric corrosion inhibitors came into limelight. This review article provides an overview of the recent development of different classes of corrosion inhibitors with special emphasis on different functional motifs of natural, synthetically modified natural, and synthetic polymeric materials. The significance, mechanism, and challenges of using polymeric materials as corrosion inhibitors are also highlighted in the review.